Formation of carbon on non-porous Ni mesh during the catalytic pyrolysis of acetylene - Lee, W.; Syed-Hassan, Syed; Li, Chun-Zhu (Elsevier, 2012)
Unsupported catalysts show great promise for the production of nanocarbon material. This study aims to investigate the formation of carbon nanofibres from the pyrolysis of acetylene using a non-porous mesh as a catalyst. Our results showed that temperature and total gas flow rate have significant effects on the formation of carbon nanofibres on the non-porous Ni mesh catalyst. Opposite effects of gas flow rate on the yield of carbon on Ni mesh surface were observed for the pyrolysis of acetylene at low (620 °C) and high (750 °C) temperature. Analysis of carbon nanofibres using scanning electron microscopy, FT-Raman spectroscopy and thermogravimetric analysis showed that the structural ordering in the produced carbon changed with the yield of carbon.